UNFAIR COMPETITION IN IMPORT E-COMMERCE: A STUDY ON THE UNIVERSITY PUBLIC PURCHASE DECISION - Aparecido Fortuoso da Silva, Givan (2024)
Considering the growth and maturation of Brazilian e-commerce promoted by COVID-19, even more so with regard to import e-commerce, and the concern that offers in this segment are supported by unfair trade practices, it was defined as general objective for the present study: to identify whether unfair competition in import e-commerce influences the purchase decision of the university public. As specific objectives were defined: to investigate the factors that influence the purchase decision of the university public, to identify the understanding about e-commerce and unfair competition. The research sample comprised students of the Higher Course in Foreign Trade at a public educational institution located in the Western Region of Greater São Paulo. The methodology is based on a survey research, with a quantitative approach, using a Mooring Matrix and the Likert scale for the elaboration and collection of data through an electronic questionnaire. A descriptive analysis of the collected data was carried out,which led to the conclusion that unfair competition influences the purchasing decision of the university public, although it is not a determining factor.